PENERAPAN KONSEP ECO-SETTLEMENT PADA SARANA PRASARANA INFRASTRUKTUR PENDUKUNG PERMUKIMAN HUNTAP (STUDI KASUS : HUNTAP PAGERJURANG DAN HUNTAP KARANGKENDAL KECAMATAN CANGKRINGAN) - Hanindya Kusuma Artati; Albani Musyafa (TEKNISIA, 2015)
Eco-settlement infrastructure planning is a concept that puts the balance of the ecosystem at a settlement. This concept is urged to apply to residential areas, especially in the area of the catchment. Huntap as a settlement area also need to apply the concept of eco-settlement. After the eruption of Merapi, Huntap development is mostly done in the area of Cangkringan which is the catchment area that supplies water in the city of Jogjakarta. The purpose of this study was to report the results of the application of eco-settlement planning on huntap in Cangkringan area. The method used in this research are: 1) Identification of the condition of settlement infrastructure that had been built 2) comparative analysis of results of this identification with the concept of eco-settlement, 3) to formulate the results of the analysis. From the analysis, we can conclude that the development of infrastructure in the dwelling in accordance with the concept of eco-settlement.